Antiphospholipid antibodies associated with alcoholic liver disease specifically recognise oxidised phospholipids. Issue 6 (1st December 2001) - Rolla, R; Vay, D; Mottaran, E; Parodi, M; Vidali, M; Sartori, M; Rigamonti, C; Bellomo, G; Albano, E
Abstract : BACKGROUND: Circulating antiphospholipid antibodies (aPL) are often detected in patients with alcoholic liver disease (ALD) but little is known about the causes of their formation. AIMS: We have evaluated whether ethanol mediated oxidative injury might promote the development of aPL in ALD. PATIENTS AND METHODS: IgG against β2 glycoprotein 1 (β2 -GP1), cardiolipin, and human serum albumin (HSA) complexed with either oxidised arachidonic acid (HSA-APP) or malondialdehyde (HSA-MDA) were assayed by ELISA in heavy drinkers with or without ALD and in healthy subjects. RESULTS: Circulating IgG recognising cardiolipin were significantly higher in ALD patients than in controls. However, anticardiolipin reactivity of ALD sera was only evident using, as the antigen, oxidised cardiolipin but not oxidation protected cardiolipin. In ALD patients, individual values of IgG antioxidised cardiolipin were associated with the titres of antibodies against HSA-MDA and HSA-APP ( r =0.68 and 0.72, respectively; p<0.0001) used as markers of oxidative stress. ALD patients also displayed increased levels of antibodies against phospholipid binding protein β2 -GP1, and individual reactivity towards oxidised cardiolipin and β2 -GP1 were highly correlated ( r =0.85; p<0.0001). IgG binding to oxidised cardiolipin, HSA-MDA, and HSA-APP was also significantly higher in β2 -GP1 positive than in β2 -GP1 negative sera. However, preadsorption of β2 -GP1 positive sera on β2 -GP1 coated ELISA plates reduced reactivity to oxidised cardiolipin by 80%, without affecting that to HSA-APP or HSA-MDA. CONCLUSIONS: Ethanol induced oxidative injury is associated with the development of antibodies targeting complexes between oxidised cardiolipin and β2 -GP1. These antibodies might account for high aPL titres observed in patients with severe ALD.